(untitled) (London, 1992)
Global Biodiversity is the most comprehensive compendium of conservation information ever published. It provides the first systematic report on the status, distribution, management, and utilisation of the planet's biological wealth
Keywords: Biodiversity,Species diversity,Biodiversity conservation